Safety and high level efficacy of the combination malaria vaccine regimen of RTS,S/AS01B with ChAd-MVA vectored vaccines expressing ME-TRAP - Rampling, T; Ewer, K; Bowyer, G; Bliss, C; Edwards, N; Wright, D; Payne, R; Venkatraman, N; Snudden, C; Poulton, I; Roberts, R; Sinden, R; et al. (Oxford University Press, 2016)
Background: The need for a highly efficacious vaccine against Plasmodium falciparum remains pressing. In this controlled human malaria infection (CHMI) study, we assessed the safety, efficacy and immunogenicity of a schedule combining two distinct vaccine types in a staggered immunization regimen: one inducing high-titer antibodies to CSP (RTS,S/AS01B) and the other inducing potent T-cell responses to TRAP using viral vectors. Method: 37 healthy malaria-naïve adults were vaccinated with either ChAd63-MVA expressing ME-TRAP and 3 doses of RTS,S/AS01B (Group 1, n=20) or 3 doses of RTS,S/AS01B alone (Group 2, n=17). CHMI was delivered by mosquito bites in 33 vaccinated subjects at week 12 after first vaccination, and 6 unvaccinated controls. Results: No SUSAR or SAEs related to vaccination were reported. Protective vaccine efficacy was observed in 14/17 (82.4%) subjects in Group 1 and 12/16 (75%) subjects in Group 2. All control subjects were diagnosed with blood stage malaria. Both vaccination regimens were immunogenic. 14 protected subjects underwent repeat CHMI 6 months after initial CHMI; 7/8 (87.5%) Group 1 subjects and 5/6 (83.3%) Group 2 subjects remained protected. Conclusion: The high level of sterile efficacy observed in this trial is encouraging for further evaluation of combination approaches using these vaccine types.